SOCIAL-PHILOSOPHICAL CONTENT OF THE CONCEPTS OF “SOCIAL PROBLEM”, “SOCIAL PROTECTION”, “SOCIAL JUSTICE” (Universal International Scientific Journal, 2026)
It is not enough to explain the social problems of the population solely through economic indicators (income, unemployment, inflation). In socio-philosophical analysis, any "problem" is a contradictory reality that manifests itself in the system of relations between human values, norms and criteria of justice, as well as institutions (state, market, family, education, neighborhood)
Keywords: social problem, social protection, social justice, social development, social inequality, poverty, unemployment, human rights, equal opportunities, social policy, state support, humanism, welfare, social stability, resource allocation, social relations, spiritual values, social responsibility.